Strategi Penilaian Autentik dalam Konteks Kurikulum 2013 - Adisel, Adisel; Sartika, Ria; Kurniasih, Siti Dewi; Fajar, Erzal Ahmad; Arianda, Riki; Saleh, Tetap Junri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the authentic assessment strategy in the context of the 2013 curriculum. The method used is the literature study method, namely by collecting material, data and information from books, journals and articles related to authentic assessment strategies in the 2013 curriculum. Authentic Assessment strategies in the context of the 2013 Curriculum are expected to facilitate assessment planning, implementation of assessments, and reporting of student assessment results. Through the 2013 curriculum, authentic assessment becomes a serious emphasis, especially for teachers. In conclusion, authentic assessment tends to focus on complex or situational tasks, enabling students to demonstrate their abilities in more authentic settings. Therefore, authentic assessment is very relevant to the integrated topic approach in learning. Keywords: 2013 Curriculum, Authentic Assessment Strategy